DISAIN TAMBANG BATUBARA BAWAH TANAH DENGAN CAD - Ketut Gunawan (Seminar Nasional Informatika (SEMNASIF), 2012)
Over time the amount of coal reserves in Indonesia that could be mined by open pit system will be increasingly depleted. Current open pit faces many challenges from various elements of society especially the problem of environmental degradation and land acquisition people. Underground mines are relatively more environmentally friendly and in contact with soil problems people relatively smaller. Advancement of information technology especially Auto CAD program can facilitate the design of underground mines.